Scuole – schulen – schools – écoles – escuelas - Francesca Belloni; Elvio Manganaro (Festival dell'Architettura Magazine, 2021)
The recent health emergency has marked a moment of crisis for the class unit that has constituted, since the first half of the nineteenth century, the minimum dimension through which our culture has organised the process of mass education. In the light of these conditions and following a debate that has been going on for more than a decade, it therefore seems unnecessary to return to the subject of schools. We have therefore decided to dedicate this issue of FAM to the school, setting it out along three lines of study, which more than others we felt it was important to try to tackle in parallel: pedagogy, language and society, identifying three areas that are in themselves autonomous, but also certainly dependent in the construction of learning spaces and in the daily experience of those who attend them, starting with children.